The ABC transporter Opp imports reduced glutathione, while Gsi imports glutathione disulfide in Escherichia coli - Lisa R. Knoke; Maik Muskietorz; Lena Kühn; Lars I. Leichert (Redox Biology)
Glutathione is the major thiol-based antioxidant in a wide variety of biological systems, ranging from bacteria to eukaryotes. As a redox couple, consisting of reduced glutathione (GSH) and its oxidized form, glutathione disulfide (GSSG), it is crucial for the maintenance of the cellular redox balance. Glutathione transport out of and into cellular compartments and the extracellular space is a determinant of the thiol-disulfide redox state of the organelles and bodily fluids in question, but is currently not well understood. Here we use the genetically-encoded, glutathione-measuring redox probe Grx1-roGFP2 to comprehensively elucidate the import of extracellular glutathione into the cytoplasm of the model organism Escherichia coli. The elimination of only two ATP-Binding Cassette (ABC) transporter systems, Gsi and Opp, completely abrogates glutathione import into E. coli's cytoplasm, both in its reduced and oxidized form. The lack of only one of them, Gsi, completely prevents import of GSSG, while the lack of the other, Opp, substantially retards the uptake of reduced glutathione (GSH).